Analytic hierarchy process‐technique for order preference by similarity to ideal solution: A multi criteria decision‐making technique to select the best dental restorative composite materials - Yadav, Ramkumar (Polymer composites, 2021)
The purpose of this paper is to investigate the optimal selection of a variety of dental composites using a hybrid analytic hierarchy process (AHP) and technique for order preference by similarity to ideal solution (TOPSIS) technique as a multi criteria decision‐making (MCDM) technique under a set of conflict Performance Defining Criteria (PDCs). The resinous matrix of the dental composite was fabricated by Bis‐GMA (51 wt%), TEGDMA (48 wt%), CQ (0.2 wt%), and EDMAB (0.8 wt%). Five dental composite compositions were created utilizing hybrid nTiO2‐Al2O3 particles with varying nTiO2 content (0, 2, 4, 6, 8 wt%). According to AHP, the following PDCs are listed in order: Cost (PDC‐13) > Vickers hardness (PDC‐4) > compressive strength (PDC‐1) > depth of cure (PDC‐5) > flexural modulus (PDC‐3) > flexural strength (PDC‐2) > degree of conversion (PDC‐11) > material stability (PDC‐12) > void content (PDC‐8) > water sorption (PDC‐9) > Density (PDC‐7) (PDC‐6). According to TOPSIS, the following are the rankings: nT2 > nT0 > nT4 > nT6 > nT8. The experimental results are connected to the ranking of several sets of dental formulations. As a result, the AHP‐TOPSIS method is one of the finest MCDM strategies for ranking under diverse PDCs.